HUBUNGAN SIKAP MAHASISWA DENGAN PROFESI BIDAN TERHADAP PRESTASI BELAJAR MAHASISWA PRODI DIII KEBIDANAN SEMESTER II UNIVERSITAS RESPATI YOGYAKARTA - Komaria Susanti (Institut Kesehatan dan Teknologi Al Insyirah, 2020)
ABSTRACT One of health worker who involve directly toward maternal and child health service is midwife. According to Raharjo (2009), there were 230.000-250.000 midwives in Indonesia. The number of midwives more than the number of villages. It is expected the midwives are competent and professional. Objective: Identifying relationship between students attitude toward midwife profession and learning achievement of second semester students of DIII Midwifery Program at Universitas Respati Yogyakarta. This was a descriptive analytic study with cross sectional approach. Population were all of second semester students of DIII Midwifery Program. Sample was 143 students taken using proportionate to population size. Result: Spearman Rank result showed that students attitude toward midwife profession significantly associated with learning achievement statistic or p value <0,05 . There were a relationship between students attitude toward midwife profession and learning achievement of second semester students of DIII Midwifery Program at Universitas Respati Yogyakarta. Keywords: attitude, midwife profession, learning achievement